An Analysis of Using Duolingo Application to Increase Students Writing Skills in Descriptive Text - Adhitya, Ferdyansyah Bagus; Rokhayati, Titi; Nugraeni, Ismawati Ike (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to describe the use of using Duolingo application to improve students’ descriptive text writing skills in grade X of SMA Negeri 5 Purworejo. Common problems faced by students include limited vocabulary, grammatical errors, and low interest and motivation in writing. To address these challenges, this research employed a Classroom Action Research (CAR) method consisting of four phases: planning, acting, observing, and reflecting. The study involved 36 students and implemented Duolingo as a technology-based interactive learning medium. The results showed that the use of Duolingo had a positive improvement on students' writing performance. Improvements were observed in student participation, timely submission of assignments, and increased observation scores for both students and teachers. Duolingo supported students in understanding sentence structure, enriching vocabulary, and engaging more actively in the learning process. Furthermore, teachers were able to deliver lessons more creatively and systematically. This research recommends incorporating technology-based applications such as Duolingo as an alternative tool in English language learning, particularly for improving students’ writing skills in a more effective and engaging way.